Have ultraviolet laser converter of non -critical phase matching doubling of frequency, frequency tripling performance concurrently - ZHAO XIAN; WANG ZHENGPING; YU FAPENG; QI HONGWEI; LIU YANQING; ZHANG SHAOJUN; XU XINGUANG (2016)
The utility model relates to a have ultraviolet laser converter of non -critical phase matching doubling of frequency, frequency tripling performance concurrently, including the base frequency light source, the contract system of restrainting, first speculum, nonlinear optical crystal, fourth wave plate, the second mirror and filter plate, the angular bisector of nonlinear optical crystal X axle and Z axle is 0 with the the polarization direction's of base frequency light contained angle 5, is the optical axis direction of fourth wave plate 0 with the the polarization direction's of base frequency light contained angle 5 is first speculum 35 with the contained angle of the center pin of light path 55 is nonlinear optical crystal gdxY1 the xCOB crystal, was x's value range 0.18 when the base frequency optical wavelength was 1064nm 0.22, was x's value range 0.11 when the base frequency optical wavelength was 1053nm 0.15. The utility model discloses do you make a gdxY1 XCOB regards as doubling of frequency and f